THE CONFLICT OF THE NORMS IN THE EXECUTION OF SECURED OBJECTS WHICH ARE ENFORCED BY LIABILITY RIGHTS WHEN THE DEBTOR IS BANKRUPT - Ana Fauzia; Deva Gama Rizky Octavia; Fathul Hamdani (Faculty of Law-Universitas Bandar Lampung, 2022)
In a transaction, for example a company's working capital credit agreement with a bank, occurs where the bank asks for collateral in the form of mortgage rights in guaranteeing the company to pay its debts to the bank. However, because the company's assetsto be pledged as collateral do not exist or are insufficient, third party assets (individual companies/shareholders/directors/commissioners) are tied up. However, problems arise when the company is unable to pay its debts to the bank and then the bank files a bankruptcy petition which results in the debtor (company) being declared bankrupt. So that in the event that the debtor has been declared bankrupt, the execution process is carried out by the curator under the authority of the supervisory judge. The execution of collateral objects when the debtor goes bankrupt is related to two main problems, namely, related to legal regulations regarding execution and the status of collateral objects related to the bankruptcy of the debtor. With regard to the legal regulations concerning execution and the status of collateral items if the debtor is bankrupt, two different arrangements were found, namely between Law no. 37 of 2004 concerning the KPKPU and Law no. 4 of 1996 concerning Mortgage Rights, so that a principle is needed to solve these problems, namely lex specialis derogate legi generalis (Special Laws beat general Laws). Therefore, based on these problems, research is carried out using normative legal research methods, by taking an approach, namely, a statute approach related to execution.